THE EFFECT OF THE USE GOOGLE CLASSROOM ON THE LEARNING EFFECTIVENESS STUDENTS IN FKIP SIMALUNGUN UNIVERSITY IN THE COVID-19 PANDEMIC - Risjunardi Damanik Junan (Sean Institute, 2021)
The spread of Covid-19 is increasing so that it has an impact on all higher education in Indonesia. Lecturers and students use distance learning using e-learning to break the covid-19 transmission chain. Lecturers and students of FKIP Simalungun University use the Google Classroom which is expected to increase the effectiveness of learning and provide convenience to lecturers and students of FKIP Simalungun University because it can be accessed anytime, anywhere. This research is related to the application of Google Classroom in student learning at FKIP Simalungun University. The purpose of this study was to determine the effect of using Google Classroom on the effectiveness of student learning at the Faculty of Teacher Training and Education, Simalungun University. Respondents consisted of 120 students and lecturers who were still active. The data collection method used is the primary data method using a questionnaire. The results of the questionnaire distributed to respondents who were analyzed using the SPSS 25 program. The results of this study indicate that there is a significant effect of the ease and usefulness of Google Classroom on the effectiveness of learning. Meanwhile, the use of Google Classroom variables does not act as an intervening variable.